Effects of Conventional and Cooperative Learning Methods on Academic Achievement of Students in Biology Based on School Location - Stella Ekeanyanwu (International Journal on Integrated Education, 2021)
This study investigated the effect of Cooperative and Conventional learning strategies on academic achievement of senior secondary school students in the Federal Capital Territory (FCT), Abuja, Nigeria relative to Urban-Rural school location. The study adopted the pretest-posttest, quasi-experimental design and was guided by three research questions and their hypotheses. A sample size of 379 was drawn from a population of 27,160 senior secondary school students (SS 11) in four public co-educational schools. A Biology Achievement Test (BAT), was used as an instrument for data collection. Descriptive and inferential statistics were used for data analysis. The results of this study indicated a significant difference between urban and rural students’ achievement in Biology when taught using cooperative learning strategy, and in favor of urban students; a significant difference between urban/rural students mean achievement in Biology when taught using conventional learning strategy, in favor of urban students; no significant difference in achievement between students taught using cooperative learning and those taught using conventional learning strategy relative to school location. It was therefore recommended amongst others, that Biology Teachers in FCT, Abuja be trained on the operating procedures of cooperative learning in addition to conventional learning strategy they are used to; and that Biology students be exposed to jigsaw II cooperative learning strategy to engender social interaction that fosters the attainment of higher academic achievement and greater retention of learned materials, as well as those of conventional learning strategies that enables repetition and drills, leading to mastery.